INTEGRATION OF BOARDING SCHOOL VALUES IN FORMAL EDUCATION TO FORM STUDENTS' CHARACTER: A CHARACTER FORMATION STUDY OF GENERATION Z STUDENTS - Nisa’, Khoirun; Wibowo, Adi; Daimah, Daimah; Nahri, Aisyah Chorijatun (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This study explores the integration of pesantren (Islamic boarding school) values into the formal education system at MI Unggulan Annawawi, aiming to shape the character of Generation Z students. Employing a qualitative field research approach, data were gathered through participatory observation, in-depth interviews, and document analysis. The findings reveal that structured programs such as congregational dhuha prayer, memorization of short surahs and nadzom, and daily supplication have a significant impact on students' religious character and discipline. However, student independence remains limited, primarily due to the absence of senior student role models. Teachers play a pivotal role as spiritual mentors and behavior models. The study concludes that continuous and adaptive mentoring strategies are essential to enhance autonomy, especially in newly established Islamic educational institutions. This research contributes to the discourse on Islamic character education in the digital age and highlights the challenges of contextualizing pesantren values for contemporary learners.